Agile Accelerator Program: From Industry-Academia Collaboration to Effective Agile Training - Steglich, Caio; Lisboa, Anielle; Prikladnicki, Rafael; Marczak, Sabrina; Móra, Michael da Costa; Olchik, Alejandro; Heck, Nelice; Rachid, Yasser; Ghidorsi, Guilherme (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 2020)
The agile accelerator program takes place in a Brazilian technology park, as a collaboration between a university and a world-renowned technology company, specialized in agile development and consulting. This partnership has 8-year long with the main goal of preparing undergraduate students to work in high-performance agile teams. This partnership created a culturally rich environment for student learning while influencing other companies to follow the same initiative within this technology park. We conducted a Case Study aiming to characterize this partnership (explaining how it works) and the resulting program, understanding the benefits to the program students. Our results point out the importance of the kind of partnership that provides an immersive learning environment to students, where students can learn empirically, with real projects and real stakeholders and how important it was for the program's former students to enter the job market. This successful enhanced students' training program on agile software development through the blending of culture between institutions can be of inspiration to those interested in aiming to bridge the gap between academia and industry.